Reactive stress tolerance in elite athletes: Differences in gender, sport type, and competitive level - Ong, N. C. H. (Cognition, Brain, Behavior, 2017)
The main aim of this study was to compare reactive stress tolerance of elite athletes according to gender, sport type, and competitive level. Performance under stress was evaluated in the case of 133 Singaporean national athletes, using the Determination Test in the Vienna Test System. A series of three-way analysis of variance revealed that in terms of speed and accuracy of responses under stress (1) female athletes performed better than male athletes, (2) open skill athletes performed better than closed skill athletes, and (3) athletes of higher competitive level performed better than their lower level counterparts. There were also no significant interaction effects between any of the factors. These findings help both applied sport psychology practitioners and coaches to achieve greater understanding of how different athletes might vary in terms of reactive stress tolerance.